Differences in time–intensity sensory profiles of sweet taste intensity of glucose between older and young adults - Wada, Hirotaka; Matsumoto, Hideki; Takagiwa, Mutsumi; Sato, Hitomi; Ishiguchi, Kyoko; Inoue, Aya; Goto, Tazuko K. (Frontiers in Nutrition, 2024)
Background: To understand age-related changes in sweet taste perception in daily life, it is important to understand taste intensity at the suprathreshold level. Previous studies have attempted to characterize the temporal aspects of human taste perception in terms of time–intensity evaluations. The perception of dynamic taste intensity in older adults increases slowly for salty taste; however, there have been no previous studies on time–intensity sensory evaluation of sweet taste in older adults. We hypothesized that older adults perceive sweet taste intensity more slowly than young adults. Methods: Fifty young and 40 older adults participated in the study and glucose solutions of 0.6 M and 1.5 M were used as stimuli. The study comprised two experiments: (1) a cup tasting test (static taste perception in the mouth), and (2) a time–intensity sensory evaluation, in which the solutions were presented using a custom-made delivery system. The intra-oral device was made to fit each participant’s dentition. Further, the level of gag reflex was taken into consideration for each participant in the design of the intra-oral device. A suction tube was placed across the posterior tongue near the throat to remove solution and saliva. The solution delivery system was controlled by an original computer program. Results: Older adults presented significantly different maximum intensity timing and slope for both concentrations compared with young adults (slope for 1.5 M, p < 0.01; others, p < 0.05). No significant differences were found between the older and young adults for reaction timing and maximum intensity. Conclusions: We conclude that older adults perceived sweetness more slowly than young adults, and ultimately perceived almost the same intensity as young adults. This is the first reported characterization of the time–intensity profile of sweet taste intensity of glucose in older adults. Using a standardized system enabled us to assess and compare feedback on taste intensities among different age groups in real-time. Based on this, we recommend older adults ‘savor to perceive sweet tastes at the same level experienced by young adults’.